Soil Bacterial Community Characteristics and Functional Analysis of Estuarine Wetlands and Nearshore Estuarine Wetlands in Qinghai Lake - Wei Ji; Zhiyun Zhou; Jianpeng Yang; Ni Zhang; Ziwei Yang; Kelong Chen; Yangong Du (Microorganisms)
Qinghai Lake, the largest inland saline lake in China, plays a vital role in wetland carbon cycling. However, the structure and function of soil bacterial communities in its estuarine and nearshore estuarine wetlands remain unclear. This study examined the effects of wetland type and soil depth on bacterial diversity, community composition, and functional potential in the Shaliu, Heima, and Daotang River wetlands using high-throughput sequencing. The results showed that wetland type and soil depth significantly influenced bacterial communities. Nearshore wetlands exhibited lower bacterial diversity in the 0–10 cm layer, while deeper soils (10–20 cm) showed greater regional differentiation. Estuarine wetlands were enriched with Proteobacteria, Actinobacteriota, and Chloroflexi, whereas nearshore wetlands were dominated by Actinobacteriota and Cyanobacteria. Functionally, estuarine wetlands had higher sulfate reduction and anaerobic decomposition potential, with Desulfovibrio, Desulfobacter, and Desulfotomaculum regulating sulfur cycling and carbon decomposition. In contrast, nearshore wetlands showed greater nitrogen fixation and organic matter degradation, facilitated by Rhizobium, Azotobacter, Clostridium, and nitrogen-fixing Cyanobacteria (e.g., Anabaena, Nostoc). Microbial metabolic functions varied by depth: surface soils (0–10 cm) favored environmental adaptation and organic degradation, whereas deeper soils (10–20 cm) exhibited lipid metabolism and DNA repair strategies for low-oxygen adaptation. These findings highlight the spatial heterogeneity of bacterial communities and their role in biogeochemical cycles, providing insights into wetland carbon dynamics and informing conservation strategies.